Clinical Aspects of Trace Elements: Zinc in Human Nutrition – Zinc Deficiency and Toxicity - Michelle M Pluhator; Alan Br Thomson; Richard N Fedorak (Canadian Journal of Gastroenterology)
Available evidence suggests that trace elements, such as zinc, once thought to have no nutritional relevance, are possibly deficient in large sections of the human population. Conditioned deficiencies have been reported to result from malabsorption syndromes, acrodermatitis enteropathica, alcoholism, gastrointestinal disease, thermal injury, chronic diseases (eg, diabetes, sickle cell anemia), and in total parenteral nutrition therapy. Awareness that patients with these problems are at risk has led health professionals to focus increasingly on the importance of zinc therapy in the prevention and treatment of deficiency. More recently zinc toxicity and its role in human nutrition and well-being have come under investigation. Reports have focused on the role of zinc toxicity in causes of copper deficiency, changes in the immune system and alterations in blood lipids. As the numerous challenges presented by the study of zinc in human nutrition are met, more appropriate recommendations for dietary and therapeutic zinc intake are being made.